Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21037/hbsn.2019.10.29
|View full text |Cite
|
Sign up to set email alerts
|

New-onset diabetes after adult liver transplantation in the Korean Organ Transplantation Registry (KOTRY) study

Abstract: Background: New-onset diabetes after transplantation (NODAT) is a serious complication following liver transplantation (LT). The present study aimed to investigate the incidence of and risk factors for NODAT using the Korean Organ Transplantation Registry (KOTRY) database.Methods: Patients with history of pediatric transplantation (age ≤18 years), re-transplantation, multi-organ transplantation, or pre-existing diabetes mellitus were excluded. A total of 1,919 non-diabetic adult patients who underwent a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
1
16
0
6
Order By: Relevance
“…We found that pre-transplant obesity (BMI ≥25 kg/m 2 ), use of steroids, and anti-metabolites were associated with a higher risk of NODM post LT. These results are in alignment with recent results published by KOTRY on NODM in the same population [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that pre-transplant obesity (BMI ≥25 kg/m 2 ), use of steroids, and anti-metabolites were associated with a higher risk of NODM post LT. These results are in alignment with recent results published by KOTRY on NODM in the same population [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in alignment with recent results published by KOTRY on NODM in the same population. 40 In order to improve the outcomes after LT, appropriate surgical technique, donor-recipient matching and optimization of immunosuppressants is essential. Also, there is a need for further research on innovative management strategies such as machine perfusion, liver support device and tissue bioengineering.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney transplant population, NODAT occurs as a metabolic complication in up to 24% of adults. In children, the incidence has increased from 3% in 2001 as reported by Al‐Uzri et al 6 to 9% in 2009 as reported by Koshy et al 6–8 …”
Section: Introductionmentioning
confidence: 90%
“…The recently published article, "New-onset diabetes after adult liver transplantation in the Korean Organ Transplantation Registry (KOTRY) study" by Man Kim et al has generated significant renewed interest in New Onset Diabetes after Transplant (NODAT) (1). NODAT was defined by International Consensus (2003) and by American Diabetes Association by the same criteria as Type 1/Type 2 diabetes.…”
mentioning
confidence: 99%